STUDI IDENTIFIKASI AKAD ASURANSI KONVENSIONAL TERHADAP PRINSIP SYARIAH (Studi Kasus Jasa Raharja Kota Kendari) - Amalia Sastia; Supriady Rusli; Ernawati Ernawati (JEP (Jurnal Ekonomi Pembangunan), 2018)
This research aims to know the mechanism of contract conventional insurance at Insurance PT Jasa Raharja Kendari and to know the level of conventional insurance contract compliance with Sharia principles on PT Jasa Raharja Insurance city of Kendari. The design of the research is qualitative, descriptive. Data collection is done using a list of guidelines for interviews. In this research that became an informant was Chairman of PT Jasa Raharja Kendari as much as 1 person, head of Unit billing and Finance Offices of PT Jasa Raharja Kendari as much as 1 person, staff employees as many as three people, and participants of the insurance of PT Services Raharja Kendari 4 people. This research uses descriptive analysis. The results showed that the existing fund management in PT Jasa Raharja Branch Kendari contain elements of gharar, and usury, maysir. The existence of elements of riba, where payment of compensation did not consider the magnitude of the premiums paid, and the victim or or his heir has the right to receive maternity benefit resulting from traffic accidents. Premiums received airplay on other investment interest-free, where the premiums include a compulsory Dues and mandatory contributions. Premium system run by PT Jasa Raharja Insurance. contains things that contain elements of gharar as seen from the Akkadian confuses used between participants and company parties, contain elements of uncertainty (gambling/maysir) in payment of the premium and the amount of earned and there are elements of unfairness on participants who died that the premiums are said to be non-refundable (charred). Monthly premiums paid by life insurance policyholders, in part is the common fund or funds together for helping royong members who died before savings/premium payers ends. In addition, there is no agreement with the customer that the Insurance Act as the provider of funds to be invested in other ventures, but insurers still be acting as the Manager of the Fund participants.